Data-driven gameplay experience balancing - Mirza-Babaei, Pejman (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais Estendidos do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The overall aim of developing a game that is fun to play is often hard to achieve due to the complexities of the game development process. An accurate understanding of player behavior and their gameplay experiences can help identify and resolve any potential problem areas before release. In this keynote, I will use commercial case studies and academic research projects to provide a summary of my work in developing new evaluation methodologies, tools and data visualizations for games UX evaluation. I will discuss approaches and provide guidelines on how game developers and researchers can benefit from gameplay data to optimize player experience.